2011
DOI: 10.1016/j.palwor.2011.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Upper Paleocene radiolarians from DSDP Sites 549 and 550, Goban Spur, NE Atlantic

Abstract: Upper Paleocene-lower Eocene sequences of mainly pelagic sediments in DSDP Sites 549 11 and 550 of Goban Spur, NE Atlantic, representing time periods of 10 and 6 m.y. respectively, 12 were examined to investigate the biotic response of radiolarians to the PETM. The 13 preservation of radiolarians in the lower Eocene sequences for both sites is poor. Upper 14 Paleocene radiolarian assemblages, representing a time interval of ~ 59-56 Ma at Site 549 15 and a much shorter period at Site 550, are generally moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…T. larnacium and P. heliastericus are found in ODP 171B and DSDP 10–94, ranging from UAZ JP11 to UAZ JE3 (Jackett et al., 2008). Furthermore, L. auxilla has been described from upper Palaeocene–lower Eocene sediments at DSDP Site 549, NE Atlantic (Liu et al., 2011). The final occurrence of this species constrains the upper limit of the interval of Thanetian to Ypresian (UAZ JE1–JE3; UA11–20) with an absolute age of ca.…”
Section: Resultsmentioning
confidence: 99%
“…T. larnacium and P. heliastericus are found in ODP 171B and DSDP 10–94, ranging from UAZ JP11 to UAZ JE3 (Jackett et al., 2008). Furthermore, L. auxilla has been described from upper Palaeocene–lower Eocene sediments at DSDP Site 549, NE Atlantic (Liu et al., 2011). The final occurrence of this species constrains the upper limit of the interval of Thanetian to Ypresian (UAZ JE1–JE3; UA11–20) with an absolute age of ca.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have noted a turnover in siliceous groups with warm‐water taxa migrating poleward (Liu et al . 2011; Oreshkina & Radionova 2014), an extinction of cold‐water taxa, and a rapid proliferation of tropical siliceous taxa across the PETM (Mitlehner 1996). It is likely that these previously seen results are not detected here due to the weakness of the silicate record in this interval, reflected in low preservation and sampling rates (Figs 1, 2).…”
Section: Discussionmentioning
confidence: 99%
“…2020), and the turnover of siliceous taxa at the PETM (Mitlehner 1996; Liu et al . 2011; Oreshkina & Radionova 2014) are three prime examples. The diversification rates for many of the groups reconstructed here are largely static, barring the most major events (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These taxa are widely reported in early and middle Eocene sediments but occur in greater abundance in the southwest Pacific at times of global warmth (Hollis, 2006). Liu et al (2011) suggested that these taxa were not valid indicators of high-latitude warming because they are found in the Palaeocene in the North Atlantic. However, their as-sumption that southwest Pacific and North Atlantic Ocean conditions would have been similar in the Palaeogene is not supported by ocean circulation models (Huber et al, 2003(Huber et al, , 2004.…”
Section: Radiolarian Biogeographic Affinitiesmentioning
confidence: 99%